How to account for operating condition variability when predicting liner operating life with DEM – A case study. (15th March 2015) - Franke, Jochen; Cleary, Paul W.; Sinnott, Matthew D.
Highlights: Wear prediction is important in liner design and for managing reline strategies. DEM can predict wear and profile evolution over life cycles for specific conditions. Real operating conditions vary limiting the ability to use DEM wear predictions. DEM wear and performance are predicted for six realistic operating scenarios. Liner wear is sensitive to the mill speed but does not vary much with fill level. Abstract: Wear prediction is important in the development and optimisation of liner design, and for helping to manage reline strategies. DEM is able to predict wear and profile evolution of liners over the life cycle for specific sets of conditions. However, real operation conditions often vary – usually in ways that are not known in advance, which limits the ability to use such model predictions in managing associated wear. In this study, we use a specific case of a tumbling mill to explore issues around the variability of wear caused by different operating conditions within the applicable range for the mill, and consider how these can be included in a modelling framework in order to assist with mill liner management.